Gérer le temps et la participation pendant l'exposé: contributions de l'analyse séquentielle et multimodale à la formation et au conseil de managers - Markaki, Vassiliki; Mondada, Lorenza (My University, 2009)
The paper aims at sketching the possible contribution of conversation analysis to a better understanding of work activities, able to inspire counselling, training and coaching interventions. Firstly, the paper shows that conversation analytic studies of work settings focus on issues that converge with members' concerns about the management of time and information as well as the organization of professional activities and of forms of participation. Although current management models offer solutions to these questions, they tend to favour general approaches which disregard the actual situated and detailed organization of work practices. Thus, detailed analysis of talk and embodied action at work provides for an alternative to these models. Secondly, the paper develops a single case analysis of an excerpt taken from the video recording of a business meeting: it shows how participants orient to time management and to the (re)organization of a PowerPoint presentation, dealing with changing participation frameworks. This detailed sequential and multimodal analysis aims at exploring in an empirical way the contributions of conversation analysis to the understanding of participants' concerns, as well as to the identification of the methods participants do mobilize in order to solve situated problems of time and information management.
Keywords: conversation analysis; sequentiality; multimodality; temporality; participation framework; professional applications; management; business meeting; PowerPoint presentation